2019
DOI: 10.1128/aem.00271-19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sublethal Thymol, Carvacrol, and trans -Cinnamaldehyde Adaptation on Virulence Properties of Escherichia coli O157:H7

Abstract: Essential oils (EOs) have demonstrated wide-spectrum antimicrobial activities and have been actively studied for their application in foods as alternative natural preservatives. However, information regarding microbial adaptive responses and changes in virulence properties following sublethal EO exposure is still scarce. The present study investigated the effect of sublethal thymol (Thy), carvacrol (Car), or trans-cinnamaldehyde (TC) adaptation on virulence gene expression and virulence properties of Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 51 publications
5
27
0
Order By: Relevance
“…Our study revealed that selected antibiotics, NIC, and benzoic acid downregulate the expression of motA and faeG genes crucial for bacterial motility and cellular adhesion. The same trend was registered on E. coli O157:H7: an important downregulation of genes related to flagella was shown for bacteria conditioned with sub-MIC doses of thymol and carvacrol [41].…”
Section: Discussionsupporting
confidence: 73%
“…Our study revealed that selected antibiotics, NIC, and benzoic acid downregulate the expression of motA and faeG genes crucial for bacterial motility and cellular adhesion. The same trend was registered on E. coli O157:H7: an important downregulation of genes related to flagella was shown for bacteria conditioned with sub-MIC doses of thymol and carvacrol [41].…”
Section: Discussionsupporting
confidence: 73%
“…Thymol has been reported to exhibit several biological activities that could reduce pathogenicity of a number of bacterial pathogens. Yuan and Yuk [37] demonstrated that thymol could reduce motility, biofilm formation, and efflux pump activity of Escherichia. coli O157:H7 with an induction of antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria have, among their survival strategies, the flexibility of altering the mRNA expression patterns in response to environmental stress [ 37 ], as for example when cultured with non-lethal concentrations of antimicrobials. Since the mechanism of action of NIC involves the alteration of the bacterial cell membrane and induces an intracellular ATP leakage [ 29 , 38 ], it can be postulated that bacteria subjected to stressful sub-lethal concentrations of NIC switch their energies from motility or virulence systems to vital and essential processes, until a more favorable environment is restored [ 39 ]. Recently, it has been demonstrated that a stress induced by thymol influences the S. typhimurium proteome, downregulating genes involved in chemotaxis, motility, and virulence [ 20 ].…”
Section: Discussionmentioning
confidence: 99%